2022
DOI: 10.1113/jp282981
|View full text |Cite
|
Sign up to set email alerts
|

Increased contribution of KCa channels to muscle contraction induced vascular and blood flow responses in sedentary and exercise trained ZFDM rats

Abstract: In resistance arteries, endothelium‐dependent hyperpolarization (EDH)‐mediated vasodilatation is depressed in diabetes. We hypothesized that downregulation of KCa channel derived EDH reduces exercise‐induced vasodilatation and blood flow redistribution in diabetes. To test this hypothesis, we evaluated vascular function in response to hindlimb muscle contraction, and the contribution of KCa channels in anaesthetised ZFDM, metabolic disease rats with type 2 diabetes. We also tested whether exercise training ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Furthermore, exercise training has been shown to upregulate NO-dependent and prostacyclin ( 29 )- and EDH ( 30 , 31 )-dependent mechanisms. Meanwhile, it is well-known that ACh-dependent vasodilation is substantially altered following endothelial dysfunction induced by hypertension ( 32 ), obesity ( 33 ), and diabetes ( 9 , 10 , 31 ). Altered ACh-dependent vasodilation may be improved by exercise training, potentially maintaining endothelial cell homeostasis ( 28 ).…”
Section: Effects Of Ach On Vascular Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, exercise training has been shown to upregulate NO-dependent and prostacyclin ( 29 )- and EDH ( 30 , 31 )-dependent mechanisms. Meanwhile, it is well-known that ACh-dependent vasodilation is substantially altered following endothelial dysfunction induced by hypertension ( 32 ), obesity ( 33 ), and diabetes ( 9 , 10 , 31 ). Altered ACh-dependent vasodilation may be improved by exercise training, potentially maintaining endothelial cell homeostasis ( 28 ).…”
Section: Effects Of Ach On Vascular Functionmentioning
confidence: 99%
“…Altered ACh-dependent vasodilation may be improved by exercise training, potentially maintaining endothelial cell homeostasis ( 28 ). We recently demonstrated that low-intensity exercise training could improve endothelial function in rats with obesity and type 2 diabetes by increasing the contribution of EDH to hind limb arterioles ( 10 ). These findings indicate an association between homeostasis of endothelial function and the ACh-dependent signaling pathway in endothelial cells.…”
Section: Effects Of Ach On Vascular Functionmentioning
confidence: 99%
See 2 more Smart Citations